2021
DOI: 10.1091/mbc.e20-01-0089
|View full text |Cite
|
Sign up to set email alerts
|

Osmosensing by WNK Kinases

Abstract: WNK kinases regulate electro-neutral cotransporters that are controlled by osmotic stress and chloride. We showed previously that autophosphorylation of WNK1 is inhibited by chloride, raising the possibility that WNKs are activated by osmotic stress. Here we demonstrate that unphosphorylated WNK isoforms 3 and 1 autophosphorylate in response to osmotic pressure in vitro, applied with the crowding agent polyethylene glycol 400 or osmolyte ethylene glycol, and that this activation is opposed by chloride. Small A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 66 publications
3
45
0
Order By: Relevance
“…Under these conditions, no differences in WNK1 phosphorylation or RVI were observed between LZ and KO cells, thereby suggesting that the effect of LRRC8A-containing channels on the modulation of the WNK1–NKCC axis is through the modulation of intracellular Cl − concentrations. Actually, direct activation of the purified kinase domain of WNK by osmolytes is promoted by reducing [Cl − ] ( 27 ), in concordance with our findings that LRRC8A-mediated Cl − efflux prevents excessive accumulation of intracellular Cl − and promotes WNK1–NKCC activation in intact cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Under these conditions, no differences in WNK1 phosphorylation or RVI were observed between LZ and KO cells, thereby suggesting that the effect of LRRC8A-containing channels on the modulation of the WNK1–NKCC axis is through the modulation of intracellular Cl − concentrations. Actually, direct activation of the purified kinase domain of WNK by osmolytes is promoted by reducing [Cl − ] ( 27 ), in concordance with our findings that LRRC8A-mediated Cl − efflux prevents excessive accumulation of intracellular Cl − and promotes WNK1–NKCC activation in intact cells.…”
Section: Discussionsupporting
confidence: 90%
“…We propose a mechanism ( Fig. 4 E ) by which activation of the p38/MSK1 pathway phosphorylates and activates the LRRC8A chloride and promotes Cl − efflux, which in turn facilitates shifting the conformational equilibrium of WNK1 from the chloride-bound inhibitory state toward the less-hydrated, active state triggered by hypertonicity ( 27 ). Thus, the combination of both direct activation of WNK1 by hyperosmotic stress and reduction in Cl − -mediated autoinhibition may represent a mechanism to ensure optimal WNK1 activation and guarantee NKCC1-mediated transport to promote RVI and cell survival in response to hypertonic environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloride binds and stabilizes an auto-inhibited dimeric configuration (14). Osmotic stress, mimicked in vitro with crowding agents (15), induces WNK1 and WNK3 to autophosphorylate (16). Crowding agents induce monomerization as measured by gel filtration and low-angle X-ray scattering.…”
mentioning
confidence: 99%
“…These mechanisms likely serve permissive roles that mitigate WNK1 inactivation during shrinkage (Goldsmith and Huang, 2021). A third study found that the purified WNK1 and WNK3 kinase domains activate in vitro in the presence of molecular crowders (Akella et al, 2021). This effect was associated with dehydration of the kinase domain, suggesting that solvent effects participate in a direct osmosensing mechanism.…”
Section: Discussionmentioning
confidence: 96%